CARIFTA TO CSME: From Free Zone to Economic and Political Union? - Sampson, Elizabeth Abigail (2017)
Regional integration schemes strengthen links between member countries (closed regionalism) which are often neighbouring countries. At the same time, collaboration with other schemes can promote solidarity. Nevertheless, integration schemes are affected by asymmetries. The Caribbean Community (CARICOM) is a regional integration scheme which faces many challenges but has the potential to reach the same level of regional integration as the European Union. This article examines the evolution, challenges, asymmetries and opportunities of CARICOM and offers recommendations.